Optimization design method for mix proportion of polyphenyl granule thermal insulation mortar

By using the three-layer step-by-step orthogonal test data structure model and matrix weight analysis method in the polystyrene particle insulation mortar, the limitations of mix ratio optimization in the existing technology are solved, and efficient and accurate mixing of polystyrene particle insulation mortar is achieved. Compared with optimization, it meets the performance requirements of national industry standards and specifications, and improves the economic and practicality of the materials.

CN119400314APending Publication Date: 2025-02-07XUZHOU XUDONG NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411465259.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing polystyrene particle insulation mortar mix ratio optimization method has limitations, it is difficult to accurately lock the optimal mix ratio, and the orthogonal test design is cumbersome and susceptible to experimental conditions and operation errors.

Method used

The three-layer orthogonal test data structure model and matrix weight analysis method are used, combined with orthogonal test design, extreme difference analysis and variance analysis are carried out, and the weight matrix of each factor affecting the test index is established to obtain the optimal mix ratio scheme and influence The order of primary and secondary factors.

Benefits of technology

It realizes the efficient and precise mix ratio optimization of polystyrene particle insulation mortar, meets the performance requirements of national industry standards and specifications, and improves the economic and practicality of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093090190000021
    Figure BDA0005093090190000021
  • Figure BDA0005093090190000031
    Figure BDA0005093090190000031
  • Figure BDA0005093090190000032
    Figure BDA0005093090190000032
Patent Text Reader

Abstract

The invention relates to an optimization design method for a mix proportion of polyphenyl granule thermal insulation mortar, and relates to the technical field of building materials, the optimization design method mainly comprises the following steps: setting test target parameters according to related specifications, selecting test raw materials, carrying out a basic mix proportion test, designing an orthogonal test according to the obtained basic mix proportion, and carrying out the optimization design of the mix proportion of the polyphenyl granule thermal insulation mortar. And carrying out range analysis and variance analysis, and finally obtaining an optimal mix proportion by adopting a matrix weight analysis method. According to the method, the influence degree of each factor on the test result and the interaction among different factors can be visually displayed by utilizing the form of combining the orthogonal test method and the matrix weight analysis method, and the test results of different factors under different levels can be more conveniently compared, so that the optimal combination scheme is screened out, and the test efficiency is improved. The defects of an existing optimization design method for the mix proportion of the polyphenyl granule thermal insulation mortar are effectively overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an optimization design method for the mix ratio of polystyrene particle thermal insulation mortar. Background Art

[0002] As an efficient and economical building insulation material, polystyrene particle insulation mortar has the core elements of cement, rubber powder, polystyrene particles, and can be flexibly added with various admixtures and additives according to actual needs to optimize and adjust performance. This insulation system has shown significant advantages in the field of exterior wall insulation, especially under the premise of meeting the same insulation performance, it greatly simplifies the construction process and effectively reduces the overall construction cost of the building. Therefore, with its excellent cost-effectiveness, it has become one of the preferred solutions that meet the current building energy-saving needs.

[0003] However, the performance optimization of polystyrene particle insulation mortar, especially the precise design of its mix ratio, has always been the focus and difficulty of research in this field. At present, the mix ratio optimization methods commonly used in the industry mostly rely on long-term accumulated experience as a preliminary guide, and then use orthogonal experiments to systematically explore the specific effects of different factors on various performance parameters of thermal insulation mortar. As an efficient experimental design method, orthogonal experiments can comprehensively evaluate the combined effects of multiple variables on the target results within a limited number of experiments, providing a scientific basis for the optimization of mix ratios.

[0004] Despite this, the existing optimization methods still have limitations and shortcomings that cannot be ignored. The primary problem is that although orthogonal tests can reveal the influence trend of various factors on the performance of thermal insulation mortar, due to the complex interactions between the various factors and the different degrees of influence on the performance parameters, it is often difficult to directly lock in the optimal mix ratio combination based on the results of orthogonal tests alone. In addition, the design and implementation process of orthogonal tests is relatively cumbersome, requiring a lot of time and resources, and the test results are easily affected by various factors such as experimental conditions and operational errors, resulting in the final mix ratio may not be the global optimal solution.

[0005] Therefore, in view of the limitations of existing methods, it is particularly urgent to explore and invent a more efficient and accurate polystyrene particle insulation mortar mix optimization design method. This not only requires the new method to fully consider and accurately quantify the interaction between various factors, but also requires the characteristics of rapid iteration and low-cost implementation, so as to further improve the economy and practicality of the insulation mortar while ensuring its comprehensive performance, which is of great significance for promoting the sustainable development of building energy conservation. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a method for optimizing the mix ratio of polystyrene particle thermal insulation mortar.

[0007] In a first aspect, the present invention provides a method for optimizing the mix ratio of polystyrene particle thermal insulation mortar, the method comprising the following steps:

[0008] According to the design requirements of national industry standards, determine the experimental design indicators for optimizing the mix ratio of polystyrene particle insulation mortar;

[0009] Select the raw materials used for the polystyrene particle insulation mortar and determine the basic mix ratio of the polystyrene particle insulation mortar;

[0010] According to the basic mix ratio of polystyrene particle insulation mortar, an orthogonal test design is carried out, and then polystyrene particle insulation mortar specimens with different mix ratios are prepared and the performance tests are carried out to obtain the performance parameter test values ​​of the polystyrene particle insulation mortar specimens with different mix ratios;

[0011] Performing range analysis and variance analysis on the performance parameter test values ​​of the polystyrene particle insulation mortar specimens with different mix ratios;

[0012] According to the experimental design indicators, experimental design factors and experimental design factor levels involved in orthogonal experimental design, a three-layer hierarchical orthogonal experimental data structure model containing indicator layer, factor layer and level layer is established;

[0013] According to the three-layer hierarchical orthogonal test data structure model, a weight matrix of each factor affecting the test index is established;

[0014] The weight matrices of each factor are added together and the average value is taken to obtain the total weight matrix. The optimal mix ratio scheme and the priority order of influencing factors are obtained according to the weight of the total weight matrix.

[0015] Furthermore, the test design index includes at least one of dry density, compressive strength, thermal conductivity, tensile strength, water absorption, softening coefficient and combustion performance.

[0016] Furthermore, the dry density, water consumption, total slurry volume and polystyrene particle volume of the polystyrene particle insulation mortar are determined by the following formula:

[0017] ρ d =S s m s +S f m f ;

[0018]

[0019] V2=K j V j =1-V1;

[0020] Where: d is the dry density of polystyrene particle insulation mortar; Ss is the hydration coefficient of cement; m s is the cement dosage; S f is the hydration coefficient of fly ash; m f is the amount of fly ash; m w is the water consumption of polystyrene particle insulation mortar; w / c is the water-binder ratio; ρ s is the cement density; ρ f is the fly ash density; ρ w is the water density; K j is the residual coefficient of polystyrene particles; V j is the packing density of polystyrene particles; V1 is the total volume of slurry; and V2 is the volume of polystyrene particles.

[0021] Furthermore, the three-layer hierarchical orthogonal test data structure model is shown in the following table:

[0022]

[0023] In the table: there are x indicators in the indicator layer; there are k factors in the factor layer, and each factor has m levels.

[0024] Furthermore, according to the three-layer hierarchical orthogonal test data structure model, the step of establishing the weight matrix of each factor affecting the test index includes the following process:

[0025] Factor A i The average value of the indicator at the jth level is m ij , if the larger the inspection index, the better, then M i =m ij On the contrary, M i =1 / m ij , establish the indicator layer matrix M;

[0026]

[0027] make And establish the factor layer matrix T;

[0028]

[0029] Calculation Factor A i The range is k i ,make And establish the factor layer matrix K;

[0030]

[0031] Using the three-layer hierarchical structure model, the weight matrix ω of each factor affecting the test index is established i =M i T i K i ;

[0032] ω i T =[ω1,ω2,L,ω km ].

[0033] Furthermore, the weight matrices of each factor are added and averaged to obtain the total weight matrix;

[0034] ω T =(ω1 T +ω2 T +L+ω x T ) / k.

[0035] In a second aspect, the present invention provides a polystyrene particle thermal insulation mortar, which is prepared by the optimization design method of the polystyrene particle thermal insulation mortar mix ratio described in any one of the first aspects.

[0036] Furthermore, the mixing ratio of the polystyrene particle thermal insulation mortar includes: a water-binder ratio of 0.7, a cellulose ether dosage of 1 kg / m 3 , the polypropylene fiber content is 1.5kg / m 3 , the hemp fiber content is 0.4kg / m 3 .

[0037] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0038] The embodiment of the present invention provides an optimization design method for a polystyrene particle thermal insulation mortar mix ratio. The optimization design method provided by the present invention mainly includes: setting test target parameters according to relevant specifications, selecting test raw materials and conducting basic mix ratio tests, designing orthogonal tests according to the obtained basic mix ratios, and performing range analysis and variance analysis thereon, and finally using a matrix weight analysis method to obtain the optimal mix ratio. The present invention utilizes a combination of the orthogonal test method and the matrix weight analysis method to intuitively display the degree of influence of each factor on the test results, as well as the interaction between different factors, and more conveniently compare the test results of different factors at different levels, thereby screening out the optimal combination scheme, and effectively making up for the deficiencies of the existing optimization design method for polystyrene particle thermal insulation mortar mix ratios. Specifically:

[0039] The existing optimization design of polystyrene particle insulation mortar mix ratio only uses range analysis and variance analysis on the results of orthogonal experiments to determine the significance of the influence of each factor on the performance of the insulation mortar. However, it is difficult to obtain the optimal mix ratio because the influence of each factor on the performance parameters is not the same.

[0040] One of the existing publicly available polystyrene particle insulation mortar ratios is: the cementitious material of the insulation mortar is a mixture of cement, fly ash, redispersible latex powder, cellulose ether, and polypropylene fiber 7kg:3kg:150g:37g:9g. The EPS particle dosage is 70%, the bone glue ratio is 5:1, and its performance is dry apparent density 417kg / m 3 ; Compressive strength 1.09MPa; Thermal conductivity 0.0725W / (m·K).

[0041] According to the DBJ01-63-2019 "Quality Inspection Standard for External Wall Insulation Polymer Mortar" and JGJ / T253-2019 "Technical Standard for Inorganic Light Aggregate Mortar Insulation System", the compression-fold ratio of the anti-cracking mortar is not greater than 3.0, and the compression-fold ratio is minimized as much as possible to enhance the crack resistance, and the dry density is ≤350kg / m 3 , compressive strength ≥ 0.4MPa, thermal conductivity ≤ 0.06W / (m·K).

[0042] The dry apparent density and thermal conductivity of the existing above-mentioned ratio do not meet the requirements of the specification. The present invention's formula was tested according to the optimized ratio, and the dry density of the optimized formula was measured to be 329.65kg / m 3 The thermal conductivity is 0.0536W / (m·K), the compressive strength is 1.44MPa, and the tensile strength is 0.8MPa. All parameters meet the requirements of the specifications, and the results show that the requirements of the optimization objectives are met. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0045] The existing polystyrene particle insulation mortar mix ratio optimization method is mainly to determine the basic mix ratio based on experience, and use orthogonal experiments to determine the influence of various factors on the performance parameters of the insulation mortar. However, since the influence of various factors on the performance parameters of the insulation mortar in the orthogonal experiment is not the same, it is difficult to obtain the optimal mix ratio relying solely on orthogonal experiments.

[0046] To solve the above problems, the technical solution provided by the present invention is as follows:

[0047] In a first aspect, the present invention provides a method for optimizing the mix ratio of polystyrene particle thermal insulation mortar, the method comprising the following steps:

[0048] Step A1: According to the design requirements of national industry standards such as DBJ01-63-2019 "Quality Inspection Standard for External Wall Insulation Polymer Mortar" and JGJ / T253-2019 "Technical Standard for Inorganic Lightweight Aggregate Mortar Insulation System", determine the test design objectives, including dry density, compressive strength, thermal conductivity, tensile strength, water absorption, softening coefficient, and combustion performance.

[0049] Step A2: Select test raw materials;

[0050] Step A3: Determine the basic mix ratio;

[0051] According to the test design objectives, the basic mix design of polystyrene particle insulation mortar was carried out;

[0052] Determine the design dry density ρ of polystyrene particle insulation mortar d ;

[0053] ρ d =S s m s +S f m f ;

[0054] Where: d is the dry density of the designed thermal insulation mortar; S s is the hydration coefficient of cement; m s is the cement dosage; S f is the hydration coefficient of fly ash; m f is the amount of fly ash;

[0055] Determine the amount of water used in polystyrene particle insulation mortar;

[0056]

[0057] Where: m w is the water consumption of polystyrene particle insulation mortar; w / c is the water-binder ratio;

[0058] In 1m 3 In the polystyrene particle insulation mortar, the total volume of the paste composed of cement, fly ash and water is V1 m 3 , the volume of polystyrene particles V2 m 3 , determined by the following formula:

[0059] V2=K j V j =1-V1;

[0060] Where: s is the cement density; ρ f is the fly ash density; ρ w is the water density; K j is the residual coefficient of polystyrene particles; V j is the bulk density of polystyrene particles;

[0061] According to the mix design method, a preliminary mix design was carried out on cement, fly ash, water-binder ratio and polystyrene particles, the amount of each component was determined, and the basic mix ratio was obtained.

[0062] Step A4: Conduct orthogonal experimental design and analyze the experimental results using two methods: range analysis and variance analysis;

[0063] Step A5: Obtain the optimal mix ratio using matrix weight analysis method;

[0064] Since the influence of various factors on the performance parameters of polystyrene particle insulation mortar in orthogonal test is different, the final mix ratio can be judged only from the optimal performance index. The matrix analysis method can more conveniently compare the test results of different factors at different levels, so as to screen out the optimal combination scheme.

[0065] According to the characteristics of orthogonal experiment, L n (m k ) There are k factors in the orthogonal table, each factor has m levels, x indicators are examined, and a three-layer hierarchical structure model is established, namely the indicator layer, factor layer and level layer, as shown in Table 1;

[0066] Table 1 Orthogonal test data structure model

[0067]

[0068]

[0069] Factor A i The average value of the indicator at the jth level is m ij , if the larger the inspection index, the better, then M i =m ij On the contrary, M i =1 / m ij , establish the indicator layer matrix M;

[0070]

[0071] make And establish the factor layer matrix T;

[0072]

[0073] Calculation Factor Ai The range is k i ,make And establish the factor layer matrix K;

[0074]

[0075] Using the three-layer hierarchical structure model, the weight matrix ω of each factor affecting the test index is established i =M i T i K i ;

[0076] ω i T =[ω1,ω2,L,ω km ];

[0077] The total weight matrix is ​​obtained by adding the weight matrices of each factor and taking the average value;

[0078] ω T =(ω1 T +ω2 T +L+ω x T ) / k;

[0079] The optimal solution and the order of importance of influencing factors can be obtained based on the weight of the total weight matrix.

[0080] In a second aspect, based on the same inventive concept, the present invention provides a polystyrene particle thermal insulation mortar, which is prepared by the optimization design method of the polystyrene particle thermal insulation mortar mix ratio described in any one of the first aspects.

[0081] The polystyrene particle thermal insulation mortar provided by the present invention is realized based on the optimization design method described in any one of the first aspects. Therefore, the polystyrene particle thermal insulation mortar has at least the beneficial effects of the technical solution described in any one of the first aspects, which will not be described one by one here.

[0082] In some specific embodiments, the mixing ratio of the polystyrene particle thermal insulation mortar includes: a water-binder ratio of 0.7, a cellulose ether dosage of 1 kg / m 3 , the polypropylene fiber content is 1.5kg / m 3 , the hemp fiber content is 0.4kg / m 3 .

[0083] It should be noted that the component raw materials involved in the optimization design method of the polystyrene particle insulation mortar mix ratio provided in the embodiment of the present invention, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out in accordance with the technical contents disclosed in the prior art or directly using existing equipment, and the present invention document will not elaborate on them one by one.

[0084] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0085] Example

[0086] The specific steps of the method for optimizing the mix ratio of polystyrene particle thermal insulation mortar provided in this example are as follows:

[0087] This example is based on the specification DBJ01-63-2019 "Quality Inspection Standard for External Wall Insulation Polymer Mortar" and JGJ / T253-2019 "Technical Standard for Inorganic Light Aggregate Mortar Insulation System". The compression-fold ratio of the anti-cracking mortar is not greater than 3.0, and the compression-fold ratio is minimized as much as possible to enhance the crack resistance. The dry density is ≤350kg / m 3 , compressive strength ≥ 0.4MPa, thermal conductivity ≤ 0.06W / (m·K), with this as the goal to optimize the original formula, the specific test design objectives are shown in Table 2.

[0088] Table 2 Experimental design objectives

[0089]

[0090]

[0091] The experimental raw materials include: ordinary 42.5 silicate cement, fly ash, water reducing agent, polystyrene particles, ordinary drinking water, latex powder, polypropylene fiber, cellulose ether, hemp fiber and calcium formate;

[0092] The commonly used auxiliary insulation material for the non-disassembly insulation formwork in engineering is an insulation mortar made by mixing aggregates, cementitious materials, admixtures, etc. in a certain proportion. According to the different insulation aggregates, it is mainly divided into polystyrene particle insulation mortar, expanded perlite insulation mortar, vitrified microsphere insulation mortar, etc. Compared with other external insulation forms, the use of polystyrene particle exterior wall insulation system can simplify construction operations and reduce construction costs while achieving the same insulation effect. It has a very high cost-effectiveness, so polystyrene particles are selected. The basic raw materials of polystyrene particle insulation mortar are cement, glue powder and polystyrene particles. On this basis, some admixtures and admixtures can be added;

[0093] Design the basic mix ratio of polystyrene particle thermal insulation mortar according to the design objectives;

[0094] The design dry density, water consumption, total slurry volume and polystyrene particle volume of polystyrene particle insulation mortar are determined by the following formula;

[0095] ρ d =S s m s +S f m f ;

[0096]

[0097] V2=K j V j =1-V1;

[0098] Where: d is the dry density of polystyrene particle insulation mortar; S s is the hydration coefficient of cement; m s is the cement dosage; S f is the hydration coefficient of fly ash; m f is the amount of fly ash; m w is the water consumption of polystyrene particle insulation mortar; w / c is the water-binder ratio; ρ s is the cement density; ρ f is the fly ash density; ρ w is the water density; K j is the residual coefficient of polystyrene particles; V j is the packing density of polystyrene particles; V1 is the total volume of slurry; V2 is the volume of polystyrene particles;

[0099] According to the mix design method, a preliminary mix design was conducted for cement, fly ash, water-binder ratio, and polystyrene particles, and the dosage of each component was determined to obtain the basic mix ratio, in which the fly ash dosage was 18%, the water-binder ratio was 0.7, the latex powder dosage was 1.5%, the calcium formate dosage was 1.5%, and the water reducer dosage was 0.1%. The final calculation yielded 1m 3The polystyrene particle insulation mortar contains 239.8kg cement, 43.2kg first-grade fly ash, 180kg water, 0.24kg water reducer, 3.6k calcium formate, 3.6kg glue powder, 0.97m 3 Polystyrene particles.

[0100] The orthogonal experimental design method was adopted, and the water-binder ratio, cellulose ether content, polypropylene fiber content, and hemp content were taken as variables, and four levels were set for them respectively, as shown in Table 3.

[0101] Table 3 Factor level table

[0102]

[0103] After determining the level of each variable, the orthogonal test method was used to determine the effects of water-binder ratio, cellulose ether content, polypropylene fiber content, and hemp content on the performance of polystyrene particle insulation mortar. 16 (4 5 ) of the orthogonal test table, and the 16 groups of ratios are arranged as shown in Table 4.

[0104] Table 4 Orthogonal test mix ratio of polystyrene particle insulation mortar

[0105]

[0106] Each group of specimens was prepared according to the orthogonal test, and the dry density, thermal conductivity and compressive strength of the specimens were measured, see Table 5.

[0107] Table 5 Test results of specimen performance

[0108]

[0109]

[0110] The results of dry density, thermal conductivity and compressive strength were subjected to range analysis, and the results are shown in Tables 6, 7 and 8 below.

[0111] Table 6 Dry density range analysis

[0112]

[0113] Table 7 Analysis of thermal conductivity range

[0114]

[0115] Table 8 Compressive strength range analysis

[0116]

[0117]

[0118] The results of the range analysis show that: (1) From the range R value of dry density, B>C>D>A, cellulose ether is the main factor affecting dry density, polypropylene fiber content and hemp fiber content are secondary factors, and the water-binder ratio has the least effect on dry density; (2) From the range R value of thermal conductivity, A>B>D>C, the effect of water-binder ratio on thermal conductivity is the main factor, and cellulose and the two fiber content are secondary factors; (3) From the range R value of compressive strength, B>A>C>D, the effect of cellulose ether and water-binder ratio on compressive strength is the main factor, and polypropylene fiber content and hemp fiber content are secondary factors.

[0119] According to the above analysis, water-to-binder ratio and cellulose ether are the main factors affecting material properties, while polypropylene fiber and hemp fiber have less influence on material properties, but variance analysis is still needed to determine the significant influencing factors.

[0120] The variance analysis of dry density, thermal conductivity and compressive strength are shown in Tables 9, 10 and 11 below.

[0121] Table 9 Dry density variance analysis table

[0122]

[0123] Table 10 Thermal conductivity variance analysis table

[0124]

[0125] Table 11 Variance analysis table of compressive strength

[0126]

[0127]

[0128] The results of variance analysis show that: (1) the order of influence of various factors on dry density is B>C>A>D. Cellulose ether has an effect on the dry density of polystyrene particle insulation mortar. Hemp fiber and water-binder ratio are classified as error terms. This result is consistent with the results of range analysis; (2) the order of influence of various factors on thermal conductivity is A>B>D>C. The water-binder ratio has a significant effect on the thermal conductivity of polystyrene particle insulation mortar. The other three factors have a relatively small effect. The rest are all classified as error terms. This result is consistent with the results of range analysis; (3) the order of influence of various factors on thermal conductivity is B>A>C>D. Cellulose ether has a significant effect on the compressive strength of polystyrene particle insulation mortar. The water-binder ratio has an effect on the compressive strength of polystyrene particle insulation mortar. The dosage of the two fibers has little effect on the compressive strength and is classified as an error term. This result is consistent with the results of range analysis.

[0129] Since the influence of various factors on the performance parameters of polystyrene particle insulation mortar in the orthogonal test is different, the final mix ratio is judged based on the optimal performance index alone. The matrix analysis method can more conveniently compare the test results of different factors at different levels, thereby screening out the optimal combination scheme.

[0130] According to the characteristics of orthogonal experiment, L 16 (4 5 ) There are 4 factors and one blank column in the orthogonal table. Each factor has 4 levels. Three indicators are examined and a three-layer hierarchical structure model is established, which are the indicator layer, factor layer and level layer, as shown in Table 12.

[0131] Table 12 Orthogonal test data structure model of polystyrene particle insulation mortar

[0132]

[0133] Establish the indicator layer matrix M;

[0134]

[0135] make And establish the factor layer matrix T;

[0136]

[0137] Calculation Factor A i The range is k i ,make and establish a horizontal layer matrix;

[0138]

[0139] Using the three-layer hierarchical structure model, the weight matrix ω of each factor affecting the test index is established i =M i T i K i ;ω i T =[ω1,ω2,L,ω km ]

[0140] The total weight matrix is ​​obtained by adding the weight matrices of each factor and taking the average value;

[0141] ω T =(ω1 T +ω2 T +L+ω x T ) / k;

[0142] According to the above matrix weight analysis process, the matrix weight analysis results can be obtained, see Table 13.

[0143] Table 13 Matrix weight analysis results

[0144]

[0145]

[0146] The results of matrix weight analysis show that the optimal mix ratio is A4B2C4D2, that is, the water-binder ratio is 0.7 and the cellulose ether dosage is 1kg / m 3 , the polypropylene fiber content is 1.5kg / m 3 , the hemp fiber content is 0.4kg / m 3 .

[0147] One of the existing publicly available polystyrene particle insulation mortar ratios is: the cementitious material of the insulation mortar is a mixture of cement, fly ash, redispersible latex powder, cellulose ether, and polypropylene fiber 7kg:3kg:150g:37g:9g. The EPS particle dosage is 70%, the bone glue ratio is 5:1, and its performance is dry apparent density 417kg / m 3 ; Compressive strength 1.09MPa; Thermal conductivity 0.0725W / (m·K).

[0148] According to the DBJ01-63-2019 "Quality Inspection Standard for External Wall Insulation Polymer Mortar" and JGJ / T253-2019 "Technical Standard for Inorganic Light Aggregate Mortar Insulation System", the compression-fold ratio of the anti-cracking mortar is not greater than 3.0, and the compression-fold ratio is minimized as much as possible to enhance the crack resistance, and the dry density is ≤350kg / m 3 , compressive strength ≥ 0.4MPa, thermal conductivity ≤ 0.06W / (m·K).

[0149] The dry apparent density and thermal conductivity of the existing above-mentioned ratios do not meet the requirements of the specifications. The patented formula was trial-produced according to the optimized ratio, and the optimized formula dry density was measured to be 329.65kg / m3; the thermal conductivity was 0.0536W / (m·K), the compressive strength was 1.44MPa, and the tensile strength was 0.8MPa. All parameters met the requirements of the specifications, and the results showed that the requirements of the optimization target were met.

[0150] In summary, the embodiment of the present invention provides an optimization design method for the mix ratio of polystyrene particle thermal insulation mortar. By combining the orthogonal test method and the matrix weight analysis method, the influence of each factor on the test results and the interaction between different factors can be intuitively displayed, and the test results of different factors at different levels can be more conveniently compared, so as to screen out the optimal combination scheme, which effectively makes up for the shortcomings of the existing optimization design method for the mix ratio of polystyrene particle thermal insulation mortar.

[0151] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0152] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for optimizing the mix ratio of polystyrene particle thermal insulation mortar, characterized in that: The optimization design method of the polystyrene particle thermal insulation mortar mix ratio comprises the following steps: According to the design requirements of national industry standards, determine the experimental design indicators for optimizing the mix ratio of polystyrene particle insulation mortar; Select the raw materials used for the polystyrene particle insulation mortar and determine the basic mix ratio of the polystyrene particle insulation mortar; According to the basic mix ratio of polystyrene particle insulation mortar, an orthogonal test design is carried out, and then polystyrene particle insulation mortar specimens with different mix ratios are prepared and performance tested, and the performance parameter test values ​​of polystyrene particle insulation mortar specimens with different mix ratios are obtained; Performing range analysis and variance analysis on the performance parameter test values ​​of the polystyrene particle insulation mortar specimens with different mix ratios; According to the experimental design indicators, experimental design factors and experimental design factor levels involved in orthogonal experimental design, a three-layer hierarchical orthogonal experimental data structure model containing indicator layer, factor layer and level layer is established; According to the three-layer hierarchical orthogonal test data structure model, a weight matrix of each factor affecting the test index is established; The weight matrices of each factor are added together and the average value is taken to obtain the total weight matrix. The optimal mix ratio scheme and the priority order of influencing factors are obtained according to the weight of the total weight matrix.

2. The optimization design method for the mix ratio of polystyrene particle thermal insulation mortar according to claim 1 is characterized in that: The test design index includes at least one of dry density, compressive strength, thermal conductivity, tensile strength, water absorption, softening coefficient and combustion performance.

3. The optimization design method for the mix ratio of polystyrene particle thermal insulation mortar according to claim 1 is characterized in that: The dry density, water consumption, total slurry volume and polystyrene particle volume of polystyrene particle insulation mortar are determined by the following formula: r d =S s m s +S f m f ; V2=K j V j =1-V1; Where: d is the dry density of polystyrene particle insulation mortar; S s is the hydration coefficient of cement; m s is the cement dosage; S f is the hydration coefficient of fly ash; m f is the amount of fly ash; m w is the water consumption of polystyrene particle insulation mortar; w / c is the water-binder ratio; ρ s is the cement density; ρ f is the fly ash density; ρ w is the water density; K j is the residual coefficient of polystyrene particles; V j is the packing density of polystyrene particles; V1 is the total volume of slurry; V2 is the volume of polystyrene particles.

4. The optimization design method for the mix ratio of polystyrene particle thermal insulation mortar according to claim 1 is characterized in that: The three-layer hierarchical orthogonal test data structure model is shown in the following table: In the table: there are x indicators in the indicator layer; there are k factors in the factor layer, and each factor has m levels.

5. The optimization design method for the mix ratio of polystyrene particle thermal insulation mortar according to claim 4 is characterized in that: According to the three-layer hierarchical orthogonal test data structure model, the step of establishing the weight matrix of each factor affecting the test index includes the following process: Factor A i The average value of the indicator at the jth level is m ij , if the larger the inspection index, the better, then M i =m ij On the contrary, M i =1 / m ij , establish the indicator layer matrix M; make And establish the factor layer matrix T; Calculation Factor A i The range is k i ,make And establish the factor layer matrix K; Using the three-layer hierarchical structure model, the weight matrix ω of each factor affecting the test index is established i =M i T i K i ; oh i T =[ω1,ω2,L,ω km ]。 6. The optimization design method for the mix ratio of polystyrene particle thermal insulation mortar according to claim 5 is characterized in that: The weight matrix of each factor is added and averaged to obtain the total weight matrix; oh T =(ω1 T +ω2 T +L+ω x T ) / k.

7. A polystyrene particle thermal insulation mortar, characterized in that: The polystyrene particle thermal insulation mortar is prepared by adopting the optimization design method of the polystyrene particle thermal insulation mortar mix ratio according to any one of claims 1 to 6.

8. The polystyrene particle thermal insulation mortar according to claim 7, characterized in that: The mixing ratio of the polystyrene particle thermal insulation mortar includes: a water-binder ratio of 0.7, a cellulose ether dosage of 1 kg / m 3 , the polypropylene fiber content is 1.5kg / m 3 , the hemp fiber content is 0.4kg / m 3 .